Perusahaan syariah dan pengungkapan corporate social responsibility: Analisis pengaruh faktor internal dan karakteristik perusahaan - Peni Nugraheni; Deasy Permatasari (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2016)
The development of the shariah compliant companies provides an alternative option for stakeholders to invest in accordance with shariah principles. Disclosure of Islamic social reporting (ISR) is an important point for shariah company to demonstrate its performance to stakeholders and also the extent to which companies carry out activities in accordance with shariah. This study examines the factors that affect the disclosure of ISR on companies listed in the List of Islamic Securities (DES) in 2014. The variables are leverage, liquidity, supporting bank, women in board of commissioners and the educational background of the board of commissioners (BOC). This research is conducted using ISR index developed by Hanifa and Hudaib (2007), which consist of four dimensions and 59 items. Statistical tests find empirical evidence that liquidity and educational background of BOC have positive effect on ISR disclosure, leverage and women in BOC has negative effect while supporting banks have no effect on the disclosure of ISR.